Inflammatory mediators are potential biomarkers for extracorporeal shockwave therapy in horses. (16th October 2019) - Chen, J.‐W.; Stefanovski, D.; Haughan, J.; Jiang, Z.; Boston, R.; Soma, L. R.; Robinson, M. A.
Summary: Background: Extracorporeal shockwave therapy (ESWT) can potentially mask painful injuries in equine athletes. Tests to detect whether a horse has received ESWT prior to competition are needed. Extracorporeal shockwave therapy is known to affect inflammatory mediators in other species, and if these mediators are altered in the horse, these could serve as biomarkers of ESWT. Objectives: To test the hypothesis that a single application of ESWT will alter the circulating protein concentrations of 10 inflammatory mediators in horse plasma. Study design: Prospective repeated measures experimental study. Methods: Eleven healthy horses were administered a single dose of ESWT on the dorsal surface of proximal MCIII. Blood samples were collected at −168, −144, −120, −96, −72, −70, −68, −66, −48, −24, −6, −4, −2, 0 h before and 2, 4, 6, 24, 48, 72, 96, 168, 336 and 504 h after ESWT. Plasma concentrations of interleukin 1 beta (IL‐1β), IL‐1 receptor antagonist (IL‐1RA), IL‐2, IL‐4, IL‐6, IL‐10, IL‐15, interferon gamma (IFN‐γ), soluble toll‐like receptor 2 (sTLR2) and tumour necrosis factor alpha (TNF‐α) were measured to assess the effects of ESWT on these mediators. Results: Baseline concentrations of inflammatory mediators did not change substantially during the week prior to ESWT. Plasma concentrations of five inflammatory factors changed following ESWT. IL‐1β and IL‐6 were significantly down‐regulated (P<0.01), while TNF‐α, IL‐1RA and TLR2 were significantly up‐regulated (P<0.01). The remaining cytokines were not significantly affected by ESWT. Main limitations: This study was performed in a small number of sedentary, healthy pasture‐kept horses using a single dose of ESWT applied to a single location. Additional studies are necessary to determine the effect of ESWT on inflammatory mediators in athletic horses undergoing treatment for musculoskeletal injuries. Conclusions: Plasma concentrations of TNF‐α, IL‐1β, IL‐1RA, IL‐6 and TLR2 were significantly affected by ESWT, and deserve further investigation as possible biomarkers of ESWT.